ISLAM DAN FUNDAMENTALISME - Abdan Syakuro; Alfia Nurhayanti; Amirul Rasyid; Asep Abdul Muhyi (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
This study aims to investigate the phenomenon of fundamentalism spread in society as part of the discussion on contemporary issues in Islam, using the Maudhu'i approach of tafsir in the Qur'an. A qualitative approach was used to collect references from accredited journals and other reliable sources. The thematic interpretation method was applied to interpret the verses,by searching for words related to fundamentalism, identifying the implied themes, and interpreting them with the help of Maudhu'i tafsir. This research highlights the problem of Islamic societies that still adhere to fundamentalist thinking, close themselves to other views, and tend to follow religious teachings rigidly without considering relevant social and historical contexts.